A study on the sexual health information needs and sexual health information seeking beahvior of undergraduate students of the University of the Philippines Diliman - Garcia, Rhianne Patricia P. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
Douglas and Fenton (2013) presented that having a better knowledge of sexual health could lead to having improved programs and projects in educating people who are sexually active, those who are curious about their sexuality, and those who are planning to engage in sexual experience. Additionally, by learning more about sexual health and having an idea on what it is, it would help in letting people understand the concepts of sexuality, sexual relationships, and its role in creating better and efficient prevention programs for sexually transmitted infections (STIs) or sexually transmitted diseases (STDs), teen pregnancy issues, and other concerns regarding sexual health.